Maltrato infantil y su incidencia en la educación de la escuela fiscal de niños Simón Bolívar de la ciudad de Machala del sexto año de básica del paralelo A, periodo lectivo 2012 - 2013. - Sánchez Asanza, Diana Maricxa (2013)
This research work was conducted in the city of Machala in school Simon Bolivar, with a study population of 100 children ( as), the levels of 6th year of parallel basic education "A" , 100 parents / mothers and 16 teachers (as).